Analisa Kelengkapan Berkas Rekam Medis Pada Bagian Koding Penyakit Di Puskesmas Tuntungan Pancur Batu - Yudica Rosalina; Eni Siswanti (Journal of Innovative and Creativity (Joecy), 2025)
Medical records can support improving the quality of health services and providing fast and accurate information, one of these methods and efforts is by implementing disease codes in medical record documents. The assignment of disease codes to medical record documents is guided by the International Classification of Diseases (ICD This type of research is qualitative research with a case study approach. The population in this study were all health workers at the Tuntungan Pancur Batu Community Health Center. The sample is part of the number and characteristics of the population. The research sample took several officers in the medical records unit at the Pancur Batu Community Health Center as research samples. The technique used in taking samples is the Simple Random Sampling technique which is included in Probability Sampling. In random sampling techniques, the population has the same chance of being sampled. The research subjects were the results of coding in medical record files and primary care applications. Research tools and materials used: stationery, notebook, primary care application on computer, ICD 10/Electronic ICD book, smartphone for documentation. The primary data collection method is to use interview techniques, observation, while the secondary data is obtained from reports, notes and analysis of medical record documents. Data processing techniques using observation. Based on the results of the research, there is not much difference between the disease codes given by the officers giving disease codes at the Tuntungan Pancur Batu Community Health Center and the codes contained in ICD 10. However, according to the author, the method of assigning codes at the Community Health Center is very prone to errors because it is not in accordance with WHO.